The impact of respiratory symptoms presence on quality of life of tobacco smokers - Dzubur Amela; Pepic Esad; Dzubur Alen; Ilvana Hasanbegovic; Jasmin Mušanovic; Nada Spasojevic (Archives of Global Professionals, 2012)
Introduction: Quality of life is a broad term that refers to the total well-being of the individual in terms of physical, psychological, emotional, mental, and social well-being, and which is in turn influenced by numerous factors including age, gender, socioeconomic status, risk factors in behavior, the environment, and the absence or presence of disease. Goal: The goal was to determine the presence of respiratory symptoms in smokers and to compare them with non-smokers as well as determine the relationship between quality of life with the frequency of respiratory symptoms from the aspect of gender, age, the environment in which they live, and the total monthly income of smokers compared to non-smokers. Material and Methods: The study was conducted on a sample of 600 subjects who were divided into two groups. The first group consisted of regular smokers (300 subjects) and the second group consisted of non-smokers. Former smokers were not included in the study. The survey questionnaire was designed on the basis of the following. A questionnaire to test the quality of life SF-36; Inventory of socioeconomic status EuroQoL; Basic respiratory symptoms were examined by MRC questionnaire (consisting of 9 questions).Results: The presence of respiratory symptoms was not associated with gender and the area of origin of the respondents, while the level of education, age, total monthly household income, and smoking status were directly related to the presence of respiratory symptoms, so that respondents with lower education levels, older ones, those with lower incomes, and smokers have more pronounced symptoms of respiratory problems. There is large negative impact of respiratory symptoms presence on respondent's quality of life. Conclusion: Smoking status were directly related to the presence of respiratory symptoms. There is large negative impact of respiratory symptoms presence on respondent's quality of life.